PENGARUH PERSEPSI HARGA, PROMOSI, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS KONSUMEN - Juniantara, I Made Adi; Sukawati, Tjokorda Gde Raka (E-Jurnal Manajemen; Vol 7 No 11 (2018)DO - 10.24843/EJMUNUD.2018.v07.i11.p06, 2018)
In Denpasar the application of online-based transport service providers experienced a very tight competition in order to get big profits. In the area of ??Denpasar itself has been operating three online service provider-based services such as Uber, Gojek and Grab. This research type of online transportation services to be selected is UberX. The research location was conducted in Denpasar city. The number of samples used were 133 respondents, sample determination using non-probability sampling method with purposive sampling technique. Data collection method used is questionnaire with path analysis technique (path analysis). The result of the research found that price perception have positive and significant influence to satisfaction, promotion have positive and significant effect to satisfaction, service quality have positive and significant effect to satisfaction, and consumer satisfaction have positive and significant influence to consumer loyalty. This shows that the better the consumer perception of price, promotion and quality of service provided will increase customer satisfaction and loyalty UberX. Keywords : price perception, promotion, service quality, satisfaction, loyalty